Double-layer single-crystal hollow ZSM-5 molecular sieve as well as preparation method and application thereof

By adopting a double-layer single-crystal hollow ZSM-5 molecular sieve and combining with aluminium phosphate modification technology, the problems of existing ZSM-5 molecular sieve are solved by restricting diffusion performance and catalyst deactivation, achieving more efficient hydrocarbon catalytic cracking, and having good industrial application value.

CN119528173AActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202311092518.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-28
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The existing hollow ZSM-5 molecular sieve has a single morphology and is mostly synthesized with a large number of organic template agents, resulting in limited diffusion performance, serious problems in carbon deposit formation and catalyst deactivation, and it is difficult to flexibly adjust the proportion of hydrocarbon products.

Method used

A double-layer single-crystal hollow ZSM-5 molecular sieve has a double-layer enclosed hollow structure and an epitaxially grown nanorod shell. The crystal structure and growth orientation are observed by high-power spherical electron microscopy, and combined with a modification method with a phospho-aluminum molar ratio of 1, the hydrothermal stability and acid retention are improved.

Benefits of technology

A higher low-carbon olefin yield and BTX yield is achieved, the ethylene/propylene ratio is improved, the ability to catalyze macromolecular hydrocarbon reaction is enhanced, and the economic and environmental protection of the process is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004418078920000111
    Figure BDA0004418078920000111
  • Figure BDA0004418078920000121
    Figure BDA0004418078920000121
  • Figure BDA0004418078920000122
    Figure BDA0004418078920000122
Patent Text Reader

Abstract

The invention relates to a double-layer single-crystal hollow ZSM-5 molecular sieve as well as a preparation method and application thereof. The double-layer single-crystal hollow ZSM-5 molecular sieve has a double-layer hollow structure, and a nanorod shell layer is arranged on the outer surface of the molecular sieve. The molecular sieve can be obtained by firstly synthesizing a specific parent molecular sieve and then carrying out alkali treatment. The double-layer single-crystal hollow ZSM-5 molecular sieve is simple in preparation method, does not need to adopt a large amount of organic template agents, is good in technical economy, and has higher low-carbon olefin yield and BTX yield and higher ethylene / propylene ratio when being applied to macromolecular catalytic reactions such as hydrocarbon catalytic cracking reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic materials and relates to a double-layer single-crystal hollow ZSM-5 molecular sieve and a preparation method and application thereof. Background Art

[0002] Catalytic materials are the technical core of the petrochemical industry and the source of technological progress in the petrochemical industry. Catalytic cracking to produce low-carbon olefins is a typical high-temperature acid-catalyzed reaction, and its important core is the development and design of catalytic materials. ZSM-5 molecular sieve has a unique pore structure, adjustable acidity and high thermal / hydrothermal stability, and is the first choice for hydrocarbon catalytic cracking catalysts. However, although its regular and orderly microporous structure enhances the selectivity of specific products, it also limits the diffusion of macromolecular hydrocarbon reactants and products, and also promotes the formation of carbon deposits, further covering active sites and causing catalyst deactivation. Constructing multi-level pores is an effective measure to solve the diffusion limitation of molecular sieves, among which hollow mesoporous ZSM-5 has its unique advantages: special intracapsular microenvironment, nanoscale multi-level pore shell and unique spatial confinement space, giving it strong acidity, excellent diffusion performance and outstanding encapsulation ability. However, the morphology of the existing hollow ZSM-5 molecular sieve is single, and most of them are synthesized using a large amount of organic templates.

[0003] Catalytic cracking of hydrocarbons is an important means of obtaining small molecule hydrocarbons such as ethylene and propylene from large molecule hydrocarbons. During the cracking process, hydrocarbons will undergo a large number of parallel and serial reactions. In addition to cracking to form small molecule hydrocarbons, they may also aromatize to form aromatic hydrocarbons. The formed aromatic hydrocarbons with side chains may continue to crack or dealkylate to form BTX light aromatic hydrocarbons, or may form heavy aromatic hydrocarbons through hydrogen transfer. In refineries, sometimes it is desirable to produce more ethylene and sometimes more propylene, depending on the needs, and it is necessary to be able to flexibly adjust the product ratio. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a hollow ZSM-5 molecular sieve having a single crystal structure and a double-layer closed hollow structure and an epitaxially grown nanorod shell. Another technical problem to be solved by the present invention is to provide a preparation method and an application method of the ZSM-5 molecular sieve.

[0005] The first aspect of the present invention provides a double-layer single-crystal hollow ZSM-5 molecular sieve, which has a double-layer closed hollow structure and an epitaxially grown nanorod shell, with an average grain size of 0.8 to 3.5 μm. The ZSM-5 molecular sieve grows along the ac axis direction, and the entire particle is a single crystal structure.

[0006] According to the present invention, it has a nanorod structure, the axial direction of the nanorod structure grows along the AC axis direction, and the growth orientation of the single crystal grains of the double-layer single crystal hollow ZSM-5 molecular sieve is consistent, which is a single crystal structure. The crystal structure and growth orientation of the double-layer single crystal hollow ZSM-5 molecular sieve can be observed by a high-power spherical aberration electron microscope.

[0007] The closed hollow structure refers to a space that does not contain the ZSM-5 molecular sieve in the crystal grains of the ZSM-5 molecular sieve, and the space is closed by a ZSM-5 molecular sieve wall having a certain thickness.

[0008] The double-layer single-crystal hollow ZSM-5 molecular sieve provided by the present invention, in one case, has a double-layer closed hollow structure and an epitaxially grown nanorod shell, the double-layer single-crystal hollow ZSM-5 molecular sieve has a grain length of 0.8-3.5 μm, a grain width of 0.5-2.0 μm, an inner hollow structure length of 0.5-2.0 μm, an inner hollow structure width of 0.3-1.0 μm, a distance between the inner hollow outer wall and the outer hollow inner wall of 200-400 nm, and an epitaxially grown nanorod length of 0.5-1.0 μm.

[0009] The grain size refers to the size of the widest part of the grain, which can be obtained by measuring the size of the widest part of the grain projection surface in the SEM or TEM image of the sample. The average grain size is obtained by selecting any 10 molecular sieve grains in the SEM or TEM image and calculating the arithmetic mean of their grain sizes. The grain length refers to the length along the ac axis, the width refers to the size perpendicular to the length direction, the inner hollow structure length refers to the size of the longest part of the inner hollow structure projection, the inner hollow structure width refers to the size perpendicular to the length direction of the inner hollow structure, and the distance between the inner hollow outer wall and the outer hollow inner wall refers to the randomly measured distance between the inner outer wall and the outer inner wall. Through the SEM or TEM image, 10 molecular sieve grains are randomly selected, and their grain length, grain width, hollow structure length, hollow structure width, and wall thickness are measured, and their arithmetic mean is calculated as the grain length, grain width, hollow structure length, hollow structure width, and wall thickness of the sample.

[0010] After the double-layer single crystal hollow ZSM-5 molecular sieve is modified under the condition of phosphorus to aluminum molar ratio of 1, the crystal retention is greater than or equal to 90%, such as 90-98% or 90.2-95%, and / or the acid retention is greater than or equal to 30%, such as 30-40% or 30.5-35%, under the condition of hydrothermal treatment at 800°C for 17 hours. This indicates that the phosphorus modification has good hydrothermal stability. The crystal retention is the ratio of the relative crystallinity of the product obtained by hydrothermally treating the molecular sieve at 800°C for 17h after the molecular sieve is modified at a phosphorus-aluminum molar ratio of 1 (referred to as the relative crystallinity after hydrothermal treatment) to the relative crystallinity of the product obtained by hydrothermally treating the molecular sieve at a phosphorus-aluminum molar ratio of 1 (referred to as the relative crystallinity before hydrothermal treatment); the acid retention is the ratio of the acid amount of the product obtained by hydrothermally treating the molecular sieve at 800°C for 17h after the molecular sieve is modified at a phosphorus-aluminum molar ratio of 1 (referred to as the acid amount after hydrothermal treatment) to the acid amount of the product obtained by hydrothermally treating the molecular sieve at a phosphorus-aluminum molar ratio of 1 (referred to as the acid amount before hydrothermal treatment). The hydrothermal treatment is carried out in a 100% by volume steam atmosphere.

[0011] The modification under the condition of phosphorus-aluminum molar ratio of 1 can be carried out by an equal volume impregnation method. One method is as follows: the molecular sieve sample is evenly spread on a watch glass or a crucible, and the phosphorus-containing solution is slowly poured onto the molecular sieve sample so that the molecular sieve sample finally presents a "slurry state", and after being stirred evenly, it is dried in an oven; then it is ground evenly and calcined at 550°C for 4 hours. Usually, the mass ratio of the phosphorus-containing solution to the molecular sieve is 1 to 3. The phosphorus-containing solution is, for example, a phosphoric acid solution or a diammonium phosphate solution or a diammonium hydrogen phosphate solution.

[0012] In the present invention, the relative crystallinity of the molecular sieve is based on the XRD standard ZSM-5 molecular sieve standard sample of Sinopec Petrochemical Research Institute Co., Ltd., and the crystallinity of the standard sample is regarded as 100%.

[0013] Preferably, the mesoporous specific surface area of ​​the double-layer single-crystal hollow ZSM-5 molecular sieve accounts for 15 to 25% of the total specific surface area.

[0014] Preferably, the mesopore volume of the double-layer single crystal hollow ZSM-5 molecular sieve accounts for 40 to 60% of the total pore volume.

[0015] In the present invention, the total specific surface area, mesopore specific surface area, micropore specific surface area and pore volume are measured by low temperature nitrogen adsorption method, the BET specific surface area is calculated by BET formula, the micropore area is calculated by t-plot, and the pore size distribution is calculated by BJH. The double-layer single crystal hollow molecular sieve of the present invention is mainly microporous structure, and is rich in mesopore and macroporous structure, which can further provide multi-directional diffusion path, expand confined space, improve accessibility of active center, and have the ability to catalyze cracking of macromolecular hydrocarbons.

[0016] The double-layer single-crystal hollow ZSM-5 molecular sieve provided by the present invention can be an H-type double-layer single-crystal hollow ZSM-5 molecular sieve or a phosphorus-containing double-layer single-crystal hollow ZSM-5 molecular sieve, and the phosphorus content of the phosphorus-containing double-layer single-crystal hollow ZSM-5 molecular sieve can be 0.5-10% by mass in terms of P2O5.

[0017] The second aspect of the present invention provides a method for preparing the double-layer single-crystal hollow ZSM-5 molecular sieve, the method comprising (A) preparing a seed molecular sieve and (B) preparing a double-layer single-crystal hollow ZSM-5 molecular sieve:

[0018] Wherein (A) preparing a seed molecular sieve comprises:

[0019] (A1) mixing a silicon source (referred to as the first silicon source), a template and water, and stirring and heating at 30 to 60° C. for 2 to 6 hours to obtain a mixed solution, referred to as the first mixed solution;

[0020] (A2) subjecting the mixed solution obtained in step (A1) to hydrothermal dynamic crystallization at 140-180° C. for 8-24 hours; for example, transferring the mixed solution to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting the mixture to hydrothermal crystallization under stirring; the obtained crystallization product is recorded as seed solution;

[0021] (B) preparing a double-layer single crystal hollow ZSM-5 molecular sieve, comprising the following steps:

[0022] (B1) dissolving an alkali source in water and stirring the water to obtain an alkali source solution;

[0023] (B2) mixing an aluminum source with water and stirring to obtain an aluminum source dispersion;

[0024] (B3) mixing a silicon source (referred to as the second silicon source) with the alkaline source solution of step (B1), and stirring at room temperature for more than 10 minutes, for example, 10 to 30 minutes;

[0025] (B4) the product of step (B3), optionally mixed with a certain amount of dilution water, is mixed with the aluminum source dispersion under stirring, for example, the aluminum source dispersion obtained in step (B2) is added; stirred at room temperature, for example, for 30 to 60 minutes, to obtain a mixed solution, referred to as a second mixed solution;

[0026] (B5) adding a certain amount of the seed solution obtained in step (A2) to the mixed solution (second mixed solution) obtained in step (B4), and stirring at room temperature, for example, for 1 to 6 hours; obtaining a mixed solution, referred to as a third mixed solution; preferably, the mass ratio of the seed solution in terms of SiO2 to the product obtained in (B4) in terms of SiO2 is 5 to 20:100;

[0027] (B6) subjecting the mixed solution obtained in step (B5) (the third mixed solution) to hydrothermal dynamic crystallization at 140 to 180° C. for 6 to 48 hours;

[0028] (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain a parent molecular sieve;

[0029] (B8) mixing the parent molecular sieve obtained in step (B7) with an alkaline solution, stirring at 60 to 90° C. for, for example, 20 to 60 min, wherein the alkaline content in the alkaline solution is 0.4 to 2.0 mol / L; obtaining a solid product; and optionally (B9) treating the solid product obtained in step (B8) to obtain an H-type double-layer single crystal hollow ZSM-5 molecular sieve.

[0030] In the present invention, the room temperature is 20-35°C.

[0031] Optionally, in step A(1), the silicon source is one or more of methyl orthosilicate or ethyl orthosilicate, and the template is one or more of tetrapropylammonium hydroxide or tetrapropylammonium bromide.

[0032] Optionally, in step A(1), the ratio of template R / SiO2 is 0.05 to 0.50, such as 0.1 to 0.4, and the ratio of H2O / SiO2 is 10 to 80, such as 25 to 65. The ratio is a molar ratio. Wherein R represents the template.

[0033] Optionally, the grain size of the seed crystal in step (A2) is 200-800 nm.

[0034] In step (B1), the concentration of the alkali source solution may be 10 to 30% by mass. The alkali source is one or more of potassium hydroxide, rubidium hydroxide or cesium hydroxide.

[0035] Optionally, the concentration of the aluminum source solution in step (B2) is 5 to 20% by mass, and the aluminum source is one or more of aluminum sulfate, aluminum nitrate, aluminum isopropoxide, sodium aluminate or aluminum chloride.

[0036] Optionally, the silicon source in step (B3) is silica sol, which can be ammonium silica sol, sodium silica sol or a mixture thereof, and the SiO2 content in the silica sol is 15 to 45% by mass, for example, it can be 15%, 25%, 30%, 45% or a content range formed by a combination of any two of these numbers as endpoints.

[0037] Optionally, the molar ratio of the mixed solution obtained in step (B4) is n(SiO2) / n(Al2O3)=20-200, such as 30-100 or 40-80 or 45-65, n(M12O) / n(SiO2)=0.2-0.5, such as 0.22-0.5 or 0.25-0.50 or 0.22-0.35, n(H2O) / n(SiO2)=50-150, such as 60-120 or 75-110. Wherein M1 represents an alkali metal, selected from one or more of K, Rb or Cs, preferably K.

[0038] Optionally, in step (B5), the SiO2 content in the seed solution accounts for 5 to 20% of the SiO2 content in the silicon source (referred to as the second silicon source) in step (B3), for example, 5 to 10% by weight.

[0039] In step (B6), the mixed solution obtained in step (B5) is subjected to hydrothermal dynamic crystallization at 140-180° C. for 6-48 hours. For example, the mixed solution obtained in step (B5) can be transferred to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner, and then subjected to hydrothermal dynamic crystallization. The dynamic crystallization is to perform a crystallization reaction on the mixed solution in a moving state, such as under stirring.

[0040] In step (B7), the product obtained in step (B6) is filtered to separate the crystallized molecular sieve from the mother liquor, and then washed to remove the mother liquor attached to the molecular sieve, which can be washed with water, and then dried and calcined. The calcination temperature is, for example, 450-600° C., such as 500-600° C., and the calcination time is 2-12 hours, such as 2 to 6 hours.

[0041] Step (B7) obtains a parent molecular sieve having solid crystals, which are rich in silicon inside and rich in aluminum outside.

[0042] Step (B8) The parent molecular sieve is mixed with an alkali solution, and stirred at 60 to 90° C. for 20 to 60 minutes to form a hollow structure. The solid is then recovered, for example, filtered, washed, for example, with water to wash away the alkali solution in the treated parent molecular sieve, and dried to obtain a solid. The alkali solution is, for example, an alkali solution containing one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide. The alkali content in the alkali solution is 0.4-2.0 mol / L, for example, 0.4-1 mol / L.

[0043] Step (B9) The solid product obtained in step (B8) is treated to obtain an H-type double-layer single crystal hollow ZSM-5 molecular sieve. One embodiment includes exchanging the solid product of (B8) such as ammonium exchange, filtering, optionally washing, and then drying and roasting. The methods of ammonium exchange, drying and roasting are well known to those skilled in the art. For example, the roasting temperature can be 500 to 600° C., and the roasting time can be 1 to 5 hours.

[0044] Phosphorus can be introduced into the H-type double-layer single-crystal hollow ZSM-5 molecular sieve to obtain a phosphorus-containing double-layer single-crystal hollow ZSM-5 molecular sieve. The method of introducing phosphorus can refer to the existing method, for example, phosphorus can be introduced into the H-type double-layer single-crystal hollow ZSM-5 molecular sieve by an impregnation method, which generally includes the steps of contacting the H-type double-layer single-crystal hollow ZSM-5 molecular sieve with an impregnation solution, drying, and roasting. The impregnation solution can be a phosphoric acid solution, an ammonium phosphate solution, a diammonium hydrogen phosphate solution, or a diammonium dihydrogen phosphate solution, or a mixture of these solutions.

[0045] The third aspect of the present invention provides an application of the double-layer single-crystal hollow ZSM-5 molecular sieve provided by the first aspect of the present invention, for example, in petrochemical and / or fine chemical industries. In one embodiment, the double-layer single-crystal hollow molecular sieve is used for catalytic cracking of hydrocarbon oil, which includes the step of contacting the hydrocarbon with the double-layer single-crystal hollow ZSM-5 molecular sieve for catalytic cracking reaction. In one embodiment, the double-layer single-crystal hollow ZSM-5 molecular sieve is a hydrogen-type molecular sieve. In one embodiment, the double-layer single-crystal hollow ZSM-5 molecular sieve contains phosphorus, which is called a phosphorus-containing double-layer single-crystal hollow ZSM-5 molecular sieve, wherein the phosphorus content can be, for example, 0.5-10% by weight.

[0046] The double-layer single crystal hollow ZSM-5 molecular sieve of the present invention has a double-layer closed hollow structure and an epitaxially grown nanorod shell layer, has a rich pore structure, can provide a multi-directional diffusion path for macromolecular reactants, improve the accessibility of the active center of the molecular sieve, and has excellent catalytic performance. The double-layer single crystal hollow ZSM-5 molecular sieve can improve the accessibility of the active site of the molecular sieve, and has the ability to catalyze macromolecular hydrocarbon reactions. For example, in the hydrocarbon catalytic cracking reaction, it can have a higher low-carbon olefin yield and BTX yield, and a higher ethylene / propylene ratio.

[0047] The method for synthesizing a double-layer single-crystal hollow ZSM-5 molecular sieve provided by the present invention can obtain the double-layer single-crystal hollow ZSM-5 molecular sieve. No large amount of organic templates are required during the synthesis process.

[0048] The double-layer single-crystal hollow ZSM-5 molecular sieve provided by the present invention can be applied to the fields of petrochemical industry, fine chemical industry, etc., such as hydrocarbon adsorption separation, catalytic cracking / cracking, and has good industrial application value. For example, the double-layer single-crystal hollow ZSM-5 molecular sieve is used for hydrocarbon catalytic cracking reaction, which can have a higher yield of light olefins (ethylene and propylene) and BTX yield, as well as a higher ethylene / propylene ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a transmission electron microscope image of the double-layer single crystal hollow ZSM-5 molecular sieve prepared in Example 1.

[0050] Figure 2 This is the Fourier transform diffraction spectrum of the double-layer single crystal hollow ZSM-5 molecular sieve prepared in Example 1, which shows that it has a single crystal structure. DETAILED DESCRIPTION

[0051] The following specific implementations are described in detail. It should be understood that the specific implementations described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0052] Low temperature nitrogen adsorption analysis, instrument: ASAP2420 physical adsorption instrument (American Mac Instrument Company). Experimental method: The first step is sample pretreatment: weigh a certain amount of sample and put it into the sample tube that has been measured by the blank, put it into the degassing treatment unit, and degas for 6 hours under the conditions of furnace temperature 300℃ and vacuum degree less than 1.33Pa. The second step is sample measurement: put the pretreated sample tube into the measurement unit, fill the Dewar flask with liquid nitrogen, enter the analysis file to start the measurement, and the measurement process is to use the static volume method to determine the adsorption isotherm, calculate the total pore volume according to the adsorption amount of P / P0=0.98, calculate the pore size distribution according to the BJH method, obtain the mesopore volume, and calculate the specific surface area using the BET formula. Test conditions: The sample is vacuum degassed at 100℃ and 300℃ for 0.5h and 6h respectively, and N2 adsorption and desorption tests are carried out at 77.4K. The adsorption and desorption of nitrogen by the purified sample under different specific pressure conditions are tested to obtain the N2 adsorption-desorption isotherm. The BET specific surface area was calculated using the BET formula, the micropore area was calculated using t-plot, and the pore size distribution was calculated using BJH.

[0053] The acid content of molecular sieves was determined using the Autochem II 2920 programmed temperature desorber from Mack, USA. Test method: Weigh 0.2g of 20-40 mesh molecular sieves in a sample tube, place it in a heating furnace, use He as carrier gas at a flow rate of 25mL / min, heat it to 600℃ at 20℃ / min, and purge it for 90min to remove impurities adsorbed on the surface of the molecular sieve. Then cool it to 150℃, keep it constant for 5min, and then introduce NH3-He gas (10% NH3 and 90% He by mass fraction) into the system for 60min of adsorption, then purge it with He for 120min until the baseline is stable to desorb physically adsorbed ammonia. Program the temperature to 600℃ at a heating rate of 10℃ / min for desorption, keep it for 60min, and the desorption is completed. TCD is used to detect changes in gas components, and the instrument automatically integrates to obtain the total acid content.

[0054] Fourier transform diffraction spectrum, measuring instrument and method: The electron microscope model is JEM-ARM200F, and the electron diffraction pattern of the electron microscope is directly photographed.

[0055] The raw materials used in the following examples and comparative examples are commercially available unless otherwise specified. The room temperature of the examples and comparative examples is 26°C.

[0056] Example 1

[0057] Prepare the seed solution:

[0058] (A1) 30.0 g of ethyl orthosilicate, 34.0 g of tetrapropylammonium hydroxide and 44.2 g of deionized water were mixed and heated at 40° C. with stirring for 4 h;

[0059] (A2) transferring the solution of step (A1) into a high pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting it to dynamic crystallization at 170° C. for 12 h;

[0060] (A3) After the crystallization is completed, the crystallized product is taken out from the reactor and recorded as seed solution 1.

[0061] Preparation of double-layer single crystal hollow ZSM-5 molecular sieve:

[0062] (B1) Add 5.21 g of potassium hydroxide to 15.63 g of deionized water and stir well;

[0063] (B2) adding 1.8 g of aluminum sulfate 18hydrate to 16.2 g of deionized water and stirring well;

[0064] (B3) 30.20 g of silica sol (sodium silica sol, silicon oxide content 30% by mass, sodium oxide content 0.22% by mass, pH 9.2) was slowly added to the alkaline source solution of step (B1), and stirred at room temperature for 30 minutes;

[0065] (B4) adding 214.47 g of deionized water to step (B3), then adding the aluminum source solution of step (B2) under stirring, and stirring at room temperature for 30 minutes to obtain a mixed solution;

[0066] (B5) adding 6.34 g of the seed solution 1 described in step (A3) to the mixed solution obtained in step (B4), and stirring at room temperature for 4 hours to obtain a mixed solution;

[0067] (B6) transferring the mixed solution obtained in step (B5) to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner, and subjecting it to hydrothermal dynamic crystallization at 170° C. for 48 h;

[0068] (B7) filtering, washing, drying and calcining the product obtained in step (B6) at 550° C. for 2 h (the same below) to obtain molecular sieve M-1;

[0069] (B8) molecular sieve M-1 and a sodium hydroxide solution with a concentration of 0.6 mol / L were mixed uniformly, the mass ratio of molecular sieve M-1 to sodium hydroxide solution was 1:10, the temperature was raised to 80°C at a heating rate of 4°C / min, and then stirred at this temperature for 30 min, filtered, washed, and dried to obtain molecular sieve M-1-J;

[0070] (B9) Mix molecular sieve M-1-J: ammonium chloride: deionized water in a mass ratio of 1:1:10, stir and heat in a water bath at 80°C for 30 min, filter, wash and dry, then mix the dried solid: ammonium chloride: deionized water in a mass ratio of 1:0.5:10, perform a second ammonium exchange, filter, wash, dry, and calcine at 550°C for 2 h to obtain a hydrogen-type double-layer single crystal hollow ZSM-5 molecular sieve, denoted as M-1-JH. Figure 1 Here is the transmission electron microscopy image. Figure 2 Its Fourier transform diffraction spectrum.

[0071] Example 2

[0072] Prepare the seed solution:

[0073] (A1) 54.8 g of ethyl orthosilicate, 29.7 g of tetrapropylammonium hydroxide and 240.5 g of deionized water were mixed and heated at 40° C. with stirring for 4 h;

[0074] (A2) transferring the solution of step (A1) into a high pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting it to dynamic crystallization at 170° C. for 12 h;

[0075] The obtained crystallization product is recorded as seed solution 2.

[0076] Preparation of double-layer single crystal hollow ZSM-5 molecular sieve:

[0077] (B1) adding 5.46 g of potassium hydroxide to 24.87 g of deionized water and stirring well to obtain an alkali source solution;

[0078] (B2) adding 1.24 g of aluminum isopropoxide to 14.26 g of deionized water and stirring to obtain an aluminum source solution;

[0079] (B3) 35.80 g of silica sol (silicon oxide content 30% by mass, same as in Example 1) was slowly added to the alkali source solution of step (B1) and stirred at room temperature for 30 minutes;

[0080] (B4) adding 181.37 g of deionized water to step (B3), then adding the aluminum source solution of step (B2) under stirring, and stirring at room temperature for 30 minutes;

[0081] (B5) adding 10.74 g of seed solution 2 to the solution of step (B4) and stirring at room temperature for 4 hours;

[0082] (B6) transferring the mixed solution obtained in step (B5) to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner, and subjecting it to hydrothermal dynamic crystallization at 170° C. for 48 h;

[0083] (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain molecular sieve M-2;

[0084] (B8) mixing molecular sieve M-2 and a sodium hydroxide solution with a concentration of 0.4 mol / L, wherein the mass ratio of molecular sieve M-2 to the alkaline solution is 1:10, heating the mixture to 80°C at a heating rate of 4°C / min, stirring the mixture at this temperature for 30 min, filtering, washing and drying to obtain molecular sieve M-2-J;

[0085] (B9) Mix molecular sieve M-2-J: ammonium chloride: deionized water in a mass ratio of 1:1:10, stir and heat in a water bath at 80°C for 30 minutes, filter, wash and dry, then mix the dried solid: ammonium chloride: deionized water in a mass ratio of 1:0.5:10, perform a second ammonium exchange, filter, wash, dry, and calcine at 550°C for 2 hours to obtain a hydrogen-type double-layer single crystal hollow ZSM-5 molecular sieve, recorded as M-2-JH.

[0086] Example 3

[0087] Prepare the seed solution:

[0088] (A1) 47.6 g of ethyl orthosilicate, 70.4 g of tetrapropylammonium hydroxide and 187.6 g of deionized water were mixed and heated at 40° C. with stirring for 4 h;

[0089] (A2) transferring the solution of step (A1) into a high pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting it to dynamic crystallization at 170° C. for 12 h;

[0090] (A3) is taken out after the crystallization is completed and recorded as seed solution 3.

[0091] Preparation of double-layer single crystal hollow ZSM-5 molecular sieve:

[0092] (B1) Add 6.70 g of potassium hydroxide to 26.80 g of deionized water and stir well;

[0093] (B2) adding 1.20 g of sodium aluminate to 10.80 g of deionized water and stirring well;

[0094] (B3) 56.80 g of silica sol (silicon oxide content 30% by mass, same as in Example 1) was slowly added to the alkali source solution of step (B1), and stirred at room temperature for 30 minutes;

[0095] (B4) adding 363.30 g of deionized water to step (B3), then adding the aluminum source solution of step (B2) under stirring, and stirring at room temperature for 30 minutes;

[0096] (B5) adding 6.34 g of the seed solution 3 obtained in step (A3) to the mixed solution obtained in step (B4), and stirring at room temperature for 4 hours;

[0097] (B6) transferring the mixed solution obtained in step (B5) to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner, and subjecting it to hydrothermal dynamic crystallization at 170° C. for 48 h;

[0098] (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain molecular sieve M-3;

[0099] (B8) mixing molecular sieve M-3 and a sodium hydroxide solution with a concentration of 1.0 mol / L, wherein the mass ratio of molecular sieve M-3 to the sodium hydroxide solution is 1:10, heating the mixture to 80°C at a heating rate of 4°C / min, stirring the mixture at the same temperature for 30 min, filtering, washing and drying the mixture to obtain molecular sieve M-3-J;

[0100] (B9) Mix molecular sieve M-3-J: ammonium chloride: deionized water in a mass ratio of 1:1:10, stir and heat in a water bath at 80°C for 30 minutes, filter, wash and dry, then mix the dried solid: ammonium chloride: deionized water in a mass ratio of 1:0.5:10, perform a second ammonium exchange, filter, wash, dry, and calcine at 550°C for 2 hours to obtain a hydrogen-type double-layer single crystal hollow ZSM-5 molecular sieve, recorded as M-3-JH.

[0101] Example 4

[0102] Prepare the seed solution:

[0103] (A1) 43.5 g of ethyl orthosilicate, 35.9 g of tetrapropylammonium hydroxide and 166.4 g of deionized water were mixed and heated at 40° C. with stirring for 4 h;

[0104] (A2) transferring the solution of step (A1) into a high pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting it to dynamic crystallization at 170° C. for 12 h;

[0105] (A3) is taken out after the crystallization is completed and recorded as seed solution 4.

[0106] Preparation of double-layer single crystal hollow ZSM-5 molecular sieve:

[0107] (B1) Add 6.50 g of potassium hydroxide to 15.17 g of deionized water and stir well;

[0108] (B2) adding 2.56 g of aluminum nitrate nonahydrate to 10.24 g of deionized water and stirring well;

[0109] (B3) 64.9 g of silica sol (15% by mass of silica content) was slowly added to the alkali source solution of step (B1), and stirred at room temperature for 30 minutes;

[0110] (B4) adding 225.39 g of deionized water to step (B3), then adding the aluminum source solution of step (B2) under stirring, and stirring at room temperature for 30 minutes;

[0111] (B5) adding 6.81 g of the seed solution 4 of step (A3) to the solution of step (B4) and stirring at room temperature for 4 hours;

[0112] (B6) transferring the mixed solution of step (B5) into a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner, and subjecting it to hydrothermal dynamic crystallization at 170° C. for 48 h;

[0113] (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain molecular sieve M-4;

[0114] (B8) mixing molecular sieve M-4 and a sodium hydroxide solution with a concentration of 0.6 mol / L, wherein the mass ratio of molecular sieve M-4 to the sodium hydroxide solution is 1:10, heating the mixture to 80° C. at a heating rate of 4° C. / min, stirring the mixture at the same temperature for 30 min, filtering, washing, and drying to obtain molecular sieve M-4-J;

[0115] (B9) The molecular sieve M-4-J: ammonium chloride: deionized water were mixed in a mass ratio of 1:1:10, stirred and heated in a water bath at 80°C for 30 min, filtered, washed, and dried, and then the dried solid: ammonium chloride: deionized water were mixed in a mass ratio of 1:0.5:10, subjected to a second ammonium exchange, filtered, washed, dried, and calcined at 550°C for 2 h to obtain a hydrogen-type double-layer single crystal hollow ZSM-5 molecular sieve, denoted as M-4-JH.

[0116] Comparative Example 1

[0117] Conventional ZSM-5 molecular sieve was purchased from Sinopec Catalyst Company Qilu Branch, with a silicon-aluminum molar ratio (SiO2 / Al2O3 of 25), and was denoted as DB1-H.

[0118] Comparative Example 2

[0119] (1) conventional ZSM-5 molecular sieve (same as ZSM-5 molecular sieve in comparative example 1) and 0.2 mol / L sodium hydroxide solution were mixed evenly, the mass ratio of ZSM-5 molecular sieve to alkaline solution was 1:10, heated and stirred at 80° C. for 30 min, filtered, washed and dried;

[0120] (2) The conventional ZSM-molecular sieve treated with alkali: ammonium chloride: deionized water were mixed in a mass ratio of 1:1:10, stirred and heated in a water bath at 80°C for 30 minutes, filtered, washed, and dried, and then the dried solid: ammonium chloride: deionized water were mixed in a mass ratio of 1:0.5:10, and the second ammonium exchange was performed, filtered, washed, dried, and calcined at 550°C for 2 hours to obtain the hydrogen molecular sieve DB2-H. It does not have a hollow structure and does not have a rod-like structure.

[0121] Comparative Example 3

[0122] Conventional ZSM-5 molecular sieve was purchased from Qilu Branch of Sinopec Catalyst Company, with a silicon-aluminum molar ratio (SiO2 / Al2O3 of 25, the same as the conventional ZSM-5 molecular sieve in Comparative Example 1).

[0123] (1) mixing the conventional ZSM-5 molecular sieve and a sodium hydroxide solution with a concentration of 1.0 mol / L, wherein the mass ratio of the ZSM-5 molecular sieve to the alkaline solution is 1:10, heating and stirring at 80° C. for 30 min, filtering, washing, and drying;

[0124] (2) The purchased ZSM-molecular sieve after alkali treatment: ammonium chloride: deionized water are mixed in a mass ratio of 1:1:10, stirred and heated in a water bath at 80°C for 30 minutes, filtered, washed, and dried, and then the dried solid: ammonium chloride: deionized water are mixed in a mass ratio of 1:0.5:10, subjected to a second ammonium exchange, filtered, washed, dried, and calcined at 550°C for 2 hours to obtain a hydrogen-type molecular sieve DB3-H, which has no rod-like structure and no hollow structure.

[0125] Table 1

[0126]

[0127]

[0128] Molecular sieve evaluation

[0129] The molecular sieves of the embodiments and comparative examples were modified and calcined under the condition of a phosphorus-aluminum molar ratio of 1:1 (the method is as follows: the molecular sieve sample is evenly spread on a watch glass or a crucible, and the phosphorus-containing solution is slowly poured onto the molecular sieve sample so that the molecular sieve sample finally presents a "slurry state", and then dried in an oven after stirring evenly; then ground evenly and calcined at 550°C for 4 hours.), aged and deactivated at 800°C and 100% water vapor for 17 hours, and 40-60 mesh particles were sieved out of the tablets and evaluated on a fixed bed microreactor FB. The model compounds were n-hexadecane and 1,3,5-triisopropylbenzene. The evaluation conditions were: reaction temperature 620°C, agent-oil ratio (mass ratio) 0.75, oil feed rate 0.4 g / min, and oil feed time 300 s. The results are listed in Tables 2 and 3.

[0130] Table 2 n-hexadecane conversion results

[0131]

[0132]

[0133] Table 3 1,3,5-triisopropylbenzene conversion results

[0134]

[0135] It can be seen from Tables 2 and 3 that, compared with the comparative example, the double-layer single crystal hollow ZSM-5 molecular sieve provided by the present invention has unique morphological characteristics and high diffusion performance, and has higher diene yield and BTX yield in the catalytic reaction of long-chain alkanes (n-hexadecane) and macromolecular cyclic hydrocarbons (1,3,5-triisopropylbenzene), and has a higher ethylene / propylene ratio.

[0136] In Tables 2 and 3, diene refers to ethylene and propylene, and BTX refers to benzene, toluene and xylene.

Claims

1. A double-layer single-crystal hollow ZSM-5 molecular sieve, wherein the double-layer single-crystal hollow ZSM-5 molecular sieve has a double-layer closed hollow structure and an epitaxially grown nanorod shell layer, and the average grain size of the double-layer single-crystal hollow ZSM-5 molecular sieve is 0.8 to 3.5 μm; the nanorods of the double-layer single-crystal hollow ZSM-5 molecular sieve grow along the ac axis direction, and the entire particle is a single crystal structure.

2. The double-layer single crystal hollow ZSM-5 molecular sieve according to claim 1, wherein: The double-layer single-crystal hollow ZSM-5 molecular sieve has a double-layer closed hollow structure and an epitaxially grown nanorod shell. The double-layer single-crystal hollow ZSM-5 molecular sieve has a grain length of 0.8-3.5 μm, a grain width of 0.5-2.0 μm, an inner hollow structure length of 0.5-2.0 μm, an inner hollow structure width of 0.3-1.0 μm, a distance between the inner hollow outer wall and the outer hollow inner wall of 200-400 nm, and an epitaxially grown nanorod length of 0.5-1.0 μm.

3. The double-layer single crystal hollow ZSM-5 molecular sieve according to claim 1, wherein: The double-layer single crystal hollow ZSM-5 molecular sieve is modified under the condition of a phosphorus-aluminum molar ratio of 1, and after hydrothermal treatment at 800° C. for 17 hours, the crystal retention degree is greater than or equal to 90% and / or the acid retention degree is greater than or equal to 30%.

4. The double-layer single crystal hollow ZSM-5 molecular sieve according to claim 1, wherein: The mesopore specific surface area of ​​the double-layer single-crystal hollow ZSM-5 molecular sieve accounts for 15-25% of the total specific surface area, and the mesopore volume accounts for 40-60% of the total pore volume.

5. A method for preparing a double-layer single-crystal hollow ZSM-5 molecular sieve, the method comprising: A. Prepare seed solution, comprising the following preparation steps: (A1) mixing a first silicon source, a template and water, and stirring at 30-60° C. for 2-6 hours; wherein the molar ratio of the template to the first silicon source calculated as SiO2 is 0.05-0.50, and the molar ratio of water to the first silicon source calculated as SiO2 is 10-80; (A2) subjecting the product of step (A1) to hydrothermal dynamic crystallization at 140-180° C. for 8-24 hours to obtain a seed solution; B. Preparation of double-layer single crystal hollow ZSM-5 molecular sieve, including the following preparation steps: (B1) dissolving an alkali source in water and stirring the water to obtain an alkali source solution; (B2) mixing an aluminum source with water and stirring to obtain an aluminum source dispersion; (B3) mixing the second silicon source solution with the alkali source solution obtained in step (B1), and stirring at room temperature, preferably for more than 10 minutes; (B4) the product of step (B3) is optionally mixed with a certain amount of dilution water, and mixed with the aluminum source dispersion obtained in step (B2) under stirring, and stirred at room temperature to obtain a mixed solution, wherein the molar ratio of n(SiO2) / n(Al2O3) is 20 to 200, the molar ratio of n(H2O) / n(SiO2) is 50 to 150, and the molar ratio of n(M12O) / n(SiO2) is 0.20 to 0.50, wherein M1 represents an alkali metal; and M1 is one or more of K, Rb, and Cs; (B5) adding a certain amount of the seed solution obtained in step (A2) to the product of step (B4), stirring at room temperature, wherein the mass ratio of the seed solution in terms of SiO2 to the product of (B4) in terms of SiO2 is 5 to 20:100; (B6) subjecting the product of step (B5) to hydrothermal dynamic crystallization at 140 to 180° C. for 6 to 48 hours; (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain a parent molecular sieve; (B8) mixing the parent molecular sieve obtained in step (B7) with an alkali solution, stirring at 60 to 90° C. for 20 to 60 min, wherein the alkali content in the alkali solution is 0.4 to 2.0 mol / L; and optionally (B9) treating the solid product obtained in step (B8) to obtain an H-type double-layer single crystal hollow ZSM-5 molecular sieve; The room temperature is 20-35°C.

6. The method according to claim 5, wherein: In step (A1), the first silicon source is one or more of methyl orthosilicate or ethyl orthosilicate, the template is one or more of tetrapropylammonium hydroxide or tetrapropylammonium bromide, and the grain size of the seed crystal in step (A2) can be 200 to 800 nm.

7. The method according to claim 5, wherein: In step (A1), the molar ratio of template R / SiO2 is 0.1-0.40, and the molar ratio of H2O / SiO2 is 25-65.

8. The method according to claim 5, wherein: The concentration of the alkali source solution in step (B1) is 10-30% by mass, and the alkali source is one or more of potassium hydroxide, rubidium hydroxide or cesium hydroxide.

9. The method according to claim 5, wherein: The concentration of the aluminum source dispersion in step (B2) is 5 to 20% by mass, and the aluminum source is one or more of aluminum sulfate, aluminum nitrate, aluminum isopropoxide, sodium aluminate or aluminum chloride.

10. The method according to claim 5, wherein: In step (B3), the second silicon source is silica sol, and the silica sol is ammonium silica sol, sodium silica sol or a mixture thereof; the SiO2 content in the silica sol is 15 to 45% by mass.

11. The method according to claim 5, wherein: The stirring time of stirring at room temperature in step (B3) is 10 to 30 minutes, the stirring time of stirring at room temperature in step (B4) is 30 to 60 minutes, the stirring time of stirring at room temperature in step (B6) is 1 to 6 hours, and the mass ratio of SiO2 in the seed solution to SiO2 in the second silicon source in step (B5) is preferably 5 to 20:100 or 5 to 10:

100.

12. Application of the double-layer single-crystal hollow ZSM-5 molecular sieve according to any one of claims 1 to 4 or the double-layer single-crystal hollow ZSM-5 molecular sieve obtained according to any one of claims 5 to 11, for example, in catalytic cracking of hydrocarbons.

Citation Information

Patent Citations

  • Hollow capsule nano ZSM-5 molecular sieve and preparation method thereof

    CN102674392A

  • Method for adsorbing and removing sulfur dioxide in flue gas through double-shell ZSM-5 molecular sieve

    CN106824064A

  • Double-shell ZSM-5 molecular sieve and preparation method thereof

    CN106829999A

  • Three-level hole shell-core ZSM-5 zeolite molecular sieve and preparation method thereof

    CN107010641A

  • Hollow B-ZSM-5 molecular sieve, and preparation method and applications thereof

    CN107628630A